Uncatalyzed direct biodiesel production from wet microalgae under subcritical conditions - Felix, Charles B. (Animo Repository, 2017)
Microalgae are one of the most promising feedstocks for the production of biodiesel. However, the conventional production of biodiesel from microalgae requires the biomass to have minimum water content after cultivation. The subsequent costs and energy consumption in the dewatering and oil extraction phases make them less attractive compared to their fossil-based fuel counterparts. A direct or in situ transesterification technique which can generate biodiesel without the need for extraction and possibly the drying process is now being investigated as a response to those issues. In an effort to further increase product yields, the process can be subjected under subcritical conditions to make it less sensitive to the moisture and free fatty acid content of the biomass and to eliminate the use of certain catalysts. The effects of three variables directly affecting the biodiesel yield under this condition were investigated. These are temperature, time, and solvent concentration. The optimum settings for each independent variable which produce the maximum biodiesel yield were also determined and validated accordingly. © 2017 IEEE.